Maintenance of a scavenger ancient food web in insular remote areas - Balza, Ulises; Dodino, Samanta; Lambertucci, Sergio A.; Kusch, Alejandro; Raya-Rey, Andrea (My University, 2024)
Vultures are among the most endangered bird species, and changes in their feeding habits due to human activities pose a significant threat to their survival. We studied aspects of the trophic ecology of Andean Condors ( Vultur gryphus) in Tierra del Fuego, an archipelago in the southernmost part of its distribution, and compared it with other six sampling sites across Argentina. We estimated the isotopic niche width, the trophic position, and the extent of marine input on condors at a large spatial scale. Andean Condors in Tierra del Fuego exhibit a unique and substantial reliance on marine food webs, which matches the known historical trophic interactions of the species. In contrast to continental Patagonia, the marine trophic input was not homogeneous among individuals, but structured in two groups along the terrestrial - marine gradient. Marine carrion provided by sea lions, seabirds and stranded cetaceans should be monitored since they can be relevant for the long-term persistence of Andean condors in the area. Moreover, the link of condors with the ocean would also include the movement of marine inputs to terrestrial environments. As most condor samples were obtained in protected areas in the terrestrial-marine interphase, this further emphasizes the importance of preserving these areas in the face of environmental change to conserve not only the species and its landscape but also specific trophic interactions.
Keywords: trophic ecology; cathartidae; vultures; global change; carrion ecology